Evaluation of barnacle (Crustacea: Cirripedia) colonisation on different fabrics to support the estimation of the time spent in water by human remains. (January 2021) - Magni, Paola A.; Tingey, Elysia; Armstrong, Nicola J.; Verduin, Jennifer
Highlights: Barnacle colonisation of clothes can aid the estimation of the minPMSI of a corpse. Barnacles can colonise neoprene within one month after placement in the ocean. Barnacles preferentially colonise neoprene, followed by satin and cotton. Barnacles have an inconsistent colonisation rate on velvet. Water temperature and type of fabric affect the number of colonising barnacles. Abstract: The estimation of the time since death (minimum Post Mortem Interval, minPMI) is an essential aspect of forensic investigations. This is particularly complex when a human body is found submerged, floating or beached in a marine environment. When a cadaver is found in a terrestrial environment the minPMI estimation is generally based on the presence of carrion insects. However, when a cadaver is found in an aquatic environment, a correct crime scene reconstruction is more complex and requires the consideration of the time the remains spent submerged underwater (minimum Post Mortem Submersion Interval, minPMSI) and/or floating (Floating Interval, FI). In marine crime scene scenarios, the use of barnacles (Crustacea: Cirripedia) has recently received some attention, due to their permanent settlement on human remains and their accompanying clothing. Previous research considered barnacle growth on human shoes, but the present research is the first to focus on the colonisation of barnacles on clothing materials (fabrics). Polystyrene floats were covered by either cotton, velvet, satin or neoprene and submerged underwater over a period of six months off the coast of Perth, Western Australia. The aims of this research were 1) the identification of marine species colonising the fabrics, with special attention to barnacles; 2) the identification of which fabric type provides the most desirable environment for colonisation; and 3) the identification of factors that affect the growth rate of the different species. Three species of barnacles, Balanus trigonus Darwin, Amphibalanus reticulatus (Utinomi) and A. variegatus (Darwin), were present in varying numbers and sizes. The colonisation process of the barnacles occurred rapidly, with the first sighting of barnacles observed within the first month on neoprene and control floats. The surface that attracted the largest number of barnacles was neoprene, followed by satin and cotton, while velvet showed an inconsistent colonisation rate. The largest size barnacles were observed on the control floats, while all fabrics showed a similar smaller size. Overall, time spent in water and water temperature had a significant positive relationship with both number and size of the colonising barnacles. This study is the first to provide information that will aid in the investigation of human remains recovered from Western Australian marine waters, using the barnacle colonisation on different fabric types.